2010
DOI: 10.1210/en.2010-0063
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 Is an Essential Determinant of On-Time Parturition in the Mouse

Abstract: IL-6 abundance in amniotic fluid and uterine tissues increases in late gestation or with infection-associated preterm labor. A role in regulation of labor onset is suggested by observations that IL-6 increases expression of genes controlling prostaglandin synthesis and signaling in isolated uterine cells, but whether IL-6 is essential for normal parturition is unknown. To evaluate the physiological role of IL-6 in parturition in mice, we investigated the effect of Il6 null mutation on the timing of parturition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
122
4
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(135 citation statements)
references
References 48 publications
5
122
4
1
Order By: Relevance
“…It has been reported that this cytokine is upregulated during amniotic infection and its upregulation correlates with an increased risk of preterm delivery (Jacobsson et al, 2003). However, as we did not observe any signs of infection, we considered the notion that IL-18 expression was high in magnum due to the presence of an unknown infection as quite unlikely and instead, this cytokine may have a yet unknown role in the control of reproduction, similar to IL-6 in mammals (Robertson et al, 2010;Thomakos et al, 2010). Concerning IL-6, its expression in the reproductive tract of hens has been described (Sundaresan et al, 2007(Sundaresan et al, , 2008.…”
Section: Discussionmentioning
confidence: 59%
“…It has been reported that this cytokine is upregulated during amniotic infection and its upregulation correlates with an increased risk of preterm delivery (Jacobsson et al, 2003). However, as we did not observe any signs of infection, we considered the notion that IL-18 expression was high in magnum due to the presence of an unknown infection as quite unlikely and instead, this cytokine may have a yet unknown role in the control of reproduction, similar to IL-6 in mammals (Robertson et al, 2010;Thomakos et al, 2010). Concerning IL-6, its expression in the reproductive tract of hens has been described (Sundaresan et al, 2007(Sundaresan et al, , 2008.…”
Section: Discussionmentioning
confidence: 59%
“…This idea is consistent with findings that EZH2 inhibition promotes fibrosis (25,26) and that PRC2 component downregulation, KDM6A/B upregulation, and H3K27me3 loss occur with wound healing (27). Of note, the consequences of H3K27 demethylation were evident as early as E15.5, 3 days prior to term; aside from the expansion in decidual macrophages that occurs during this period (28, 29) (and likely explained by our observation of Csf1 upregulation), changes this early might have been missed in other studies that focused on the terminal stages of pregnancy (29,30). Interestingly, the lack of correlation between uterine H3K27me3 dynamics and uterine transcript levels for KDM6A/B and PRC2 components implicates posttranscriptional mechanisms as the ultimate determinants of H3K27 methylase and demethylase activities in DSCs.…”
Section: Discussionmentioning
confidence: 75%
“…Indeed, DSCs are generated from ESCs in vitro through the use of medroxyprogesterone acetate (a nonmetabolizable progestin), frequently in combination with a cAMP analog and/or estrogen, whereas we found that the systemic hormonal environment of early pregnancy, which includes high P4 levels, is insufficient to induce H3K27me3 accrual in mouse ESCs in vivo, as discussed above. Second, it is possible that in vitro decidudecidual activation and term parturition in humans rather than inflammation, as currently thought (2,30,32). The actual nature of H3K27me3 dynamics in human DSCs in vivo remains to be determined, however, with 2 genome-wide studies to date showing that H3K27me3 levels remain relatively constant or decline slightly when ESCs are decidualized in vitro over a 1-to 2-week period (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…This would be relevant given that IL-6 has been established as an essential determinant of on-time parturition in mice [57]. In addition, IL-6 is an IL-17-inducing cytokine secreted by synovial fibroblasts of RA patients [53].…”
Section: Discussionmentioning
confidence: 99%